Institutional Development and Good Governance in the Highway Sector : Learning from Gujarat - Bandyopadhyay, Arnab; Stankevich, Natalya (World Bank, Washington, DC, 2017)
The World Bank financed the Gujarat State Highway Project (GSHP) during 2001-07. The project development objective was to enhance the capacity of the Government of Gujarat (GOG) for effective and efficient planning and management of road infrastructure, while concurrently maximizing existing road infrastructure asset productivity through priority investments and increased maintenance funding. The project not only achieved its objective and targets successfully, but also was implemented with a significant cost reduction (about 23 percent). The GSHP resulted in a reduction in the backlog of major maintenance and an improved network to meet rapidly growing transport demand in the state. The project had the unique distinction of no contract disputes, a rarity among the highway development projects in India. The project also set best practices in developing and managing a very comprehensive asset management system, state of the art quality assurance framework and a very comprehensive training and capacity building program. The annual road sector allocation has grown from USD 30 million in 1995-1996 to an impressive USD 610 million in 2010-11, currently the second largest among all the Indian states. This study attempts to identify the key elements of the Gujarat road sector reforms and explores whether and, if so, how such reforms can be replicated across other Indian states and possibly even in other countries in the region.